A Metagenomic Nanopore Sequence Analysis Combined with Conventional Screening and Spectroscopic Methods for Deciphering the Antimicrobial Metabolites Produced by Alcaligenes faecalis Soil Isolate MZ921504 - Mohamed A. Eltokhy; Bishoy T. Saad; Wafaa N. Eltayeb; Mona R. El-Ansary; Khaled M. Aboshanab; Mohamed S. E. Ashour (MDPI AG, 2021)
The continuous development of multidrug resistance pathogens with limited therapeutic options has become a great problem globally that impose sever health hazards. Accordingly, searching for of new antimicrobials became an urgent demand and great challenge. Soil significantly have been associated with several species that are antibiotic producers. In this study, combination of conventional screening methods with Liquid chromatography- Mass spectroscopy (LC/MS) and metagenomic nanopore sequence analysis have been conducted for the deciphering the active metabolites produced by soil isolate(s). Preliminary soil screening resulted in a Gram-negative isolate identified via 16S ribosomal RNA as Alcaligenes faecalis isolate MZ921504 with promising antimicrobial activities against wide range of MDR gram-positive and gram-negative pathogens. The LC/MS analysis of the metabolites of A. faecalis isolate MZ921504 confirmed the presence of ectoine, bacillibactin, quinolobactin and burkholderic acid. Metagenomics sequence analysis of the soil sample (NCBI GenBank accession PRJNA771993) revealed the presence of conserved biosynthetic gene clusters of ectoine, bacteriocin, bacillibactin, quinolobactin, terpene and burkholderic acid of A. faecalis. In conclusion, A. faecalis isolate MZ921504 is a promising source for antimicrobial metabolites. LC/MS spectral analysis and third generation sequencing tools followed by secondary metabolite gene clusters analysis are useful methods to predict the nature of the antimicrobial metabolites.